2024
DOI: 10.3389/fenrg.2024.1326558
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic feasibility assessment and performance analysis of standalone solar photo voltaic-biomass hybrid system with optimized storage: a case study—Grand Bassa, Liberia

Jackson G. White,
Ravi Samikannu,
Moses Tunde Oladiran
et al.

Abstract: Introduction: Liberia has a significant obstacle in terms of restricted power accessibility, as only 26.7% of its populace have access to electrical energy. To tackle this issue, there is a collaborative effort between the government and private sector to undertake energy projects aimed at enhancing the power supply of the grid. The purpose of this study is to evaluate the techno-economic feasibility and analyze the performance of a standalone biomass/solar photovoltaic (PV) hybrid energy system for a rural Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Using multiple energy sources in hybrid energy systems enhances power supply consistency and reliability, mitigating weather changes and maintaining a consistent electrical supply even when a single energy source is not operating at maximum capacity (Adaramola et al, 2014;Come et al, 2021). Numerous studies have shown that hybrid power systems are more reliable and cost-effective than single-source energy systems based on viability, dependability, and economic assessments (Nfah and Ngundam, 2008;Ajao et al, 2011;Adaramola et al, 2012a;Tijani et al, 2014;Oladigbolu et al, 2019;Yimen et al, 2020;Al-Rawashdeh et al, 2023a;White et al, 2024). Moreover, integrating diverse energy sources might lead to long-term cost reductions compared to depending only on a single form of renewable energy system (Oladigbolu et al, 2019;Yimen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Using multiple energy sources in hybrid energy systems enhances power supply consistency and reliability, mitigating weather changes and maintaining a consistent electrical supply even when a single energy source is not operating at maximum capacity (Adaramola et al, 2014;Come et al, 2021). Numerous studies have shown that hybrid power systems are more reliable and cost-effective than single-source energy systems based on viability, dependability, and economic assessments (Nfah and Ngundam, 2008;Ajao et al, 2011;Adaramola et al, 2012a;Tijani et al, 2014;Oladigbolu et al, 2019;Yimen et al, 2020;Al-Rawashdeh et al, 2023a;White et al, 2024). Moreover, integrating diverse energy sources might lead to long-term cost reductions compared to depending only on a single form of renewable energy system (Oladigbolu et al, 2019;Yimen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%